Prospects for Ecumenical Ethical Witness - Iosso, Christian (The ecumenical review, 2018)
Ecumenical ethics is in need of a methodology for identifying when a common moral witness exists across communions, despite apparent dissimilarities. This essay illustrates, via the case of ecological witness, the promise of internally differentiated convergence as a conceptual catalyst for that identification. Differentiated convergence is linked here with a multidimensional account of ethics to enable close examination of the ecclesial documents of the Evangelical Lutheran Church in America (ELCA), the Presbyterian Church (PCUSA), and the United Methodist Church (UMC) - three traditions whose diverse ethical approaches and positions historically have been sources of ecumenical disagreement and contention. This investigation results in (1) the demonstration of a convergent ecumenical witness on the issue of climate change and (2) a methodological contribution to ecumenical ethics.